The Use of Yoodli as Media to Improve Speaking Skill in English Education Students - Suharso, Mu’ammar; Dalimunthe, Ahmad Amin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to determine whether there is a substantial relationship among the speaking ability of second-year students at the Public Islamic High School in Medan, assessed through an experimental and control group methodology. The present study's sample comprised 68 students from class XI Sains A 1 & XI Sains A 2. The data were collected through the implementation of two distinct evaluation tools: namely, a speaking test utilising the yoodli platform in class A1 and a test without the use of yoodli in class A2. The findings of this study indicated that second-year students at Public Islamic High School in Medan demonstrated higher academic performance in their classes that utilised the Yoodli system compared to those who did not employ it. The study's findings revealed a substantial improvement in the speaking proficiency of the institution in question. The coefficient correlation had a Rxy distribution of 0.306. This signifies a significant disparity between the two groups. It can therefore be concluded that the use of Yoodli significantly impacts the improvement of verbal proficiency.